2022
DOI: 10.3390/plants11192523
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Transcriptomic Analyses Reveal the Mechanisms of Compensatory Growth Ability for Early Rice after Low Temperature and Weak Light Stress

Abstract: “Late spring coldness” (T) is a frequent meteorological disaster in the spring in southern China, often causing severe yield losses of direct-seeded early rice. In this study, we investigated the mechanisms underlying the differences in the compensatory growth ability of different rice genotypes by focusing on agronomic traits, physiological indicators, and transcriptome. The results showed that there were significant differences in the compensatory growth recovery ability of different genotypes after a combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 42 publications
(41 reference statements)
3
14
0
Order By: Relevance
“…Interestingly, we noticed that the soluble sugar content, ROS content, CAT activity and APX activity of WT were decreased after cold stress in this study. Further, we found similar results of soluble sugar content (Wang et al, 2022;Xu et al, 2023), ROS content (Wang et al, 2022;Shu et al, 2023) and antioxidative enzyme activity (Wang et al, 2022, Liu et al, Hao et al, 2022Liu et al, 2022) have been reported in previous studies. This results probably due to the impairment of the physiological metabolic sites of soluble sugar, ROS, CAT and APX by cold stress (Hao et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly, we noticed that the soluble sugar content, ROS content, CAT activity and APX activity of WT were decreased after cold stress in this study. Further, we found similar results of soluble sugar content (Wang et al, 2022;Xu et al, 2023), ROS content (Wang et al, 2022;Shu et al, 2023) and antioxidative enzyme activity (Wang et al, 2022, Liu et al, Hao et al, 2022Liu et al, 2022) have been reported in previous studies. This results probably due to the impairment of the physiological metabolic sites of soluble sugar, ROS, CAT and APX by cold stress (Hao et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…This results probably due to the impairment of the physiological metabolic sites of soluble sugar, ROS, CAT and APX by cold stress (Hao et al, 2022). In addition, the soluble sugar content, ROS content, CAT activity and APX activity of plants fluctuated under cold stress (Wang et al, 2022;Xu et al, 2023;Shu et al, 2023), rather than continuous increasing or decreasing, resulting in decreased content or activity of the physiological characteristics in a period of time after cold stress.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the growth of rice seedlings is severely hindered when the average temperature is below 12°C ( Sipaseuth et al., 2007 ). In our previous study, we found that strong growth recovery rice variety had stronger antioxidant capacity, nitrogen metabolism capacity and higher levels of growth promoting hormones compared to weak growth recovery variety after low temperature and weak light stress ( Wang et al., 2022a ). It has been shown that the rapid growth recovery of rice seedlings after stress is also closely linked to their nitrogen utilization ( Liu et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous experiments, we found significant differences in the growth recovery ability of different early rice varieties after low temperature and weak light stress when simulating “late spring coldness” weather. Accordingly, we conducted screening tests on 131 early rice varieties and investigated the mechanism of differences between strong and weak growth recovery materials ( Wang et al., 2022a ; Wang et al., 2023 ). In order to investigate the effects of supplemental nitrogen fertilization on the growth indexes, osmoregulatory substances, nitrogen accumulation, related enzyme activities, and endogenous hormones of rice after the stress, we chose two materials with clearly different growth recovery abilities after the stress and conducted a bucket experiment in an artificial climate chamber with different N concentration treatments.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, after low temperature stress, the number of main roots, total root length, total root surface area, and total root volume of rice were signi cantly lower than the control, indicating signi cant inhibition of root growth, and the growth of above ground parts was also signi cantly weaker than the control. Previous studies have shown that the seedling height, leaf age, and fresh weight of the above ground parts are signi cantly lower than those of the control after low temperature stress [33], indicating that there is growth inhibition in both the above ground and underground parts after low temperature stress. It is worth noting that root length and seedling height are the most signi cant characteristics of our research, which is consistent with the research results of Hsu [37].…”
Section: Discussionmentioning
confidence: 85%